The Bethesda System for Reporting Thyroid Cytopathology Definitions, Criteria and Explanatory Notes - Ali, Syed Z.; Cibas, Edmund S. (Springer US : Imprint: Springer, 2010)
Thyroid fine needle aspiration is one of the most commonly performed cytologic procedures and is the standard diagnostic method for managing the patient with a thyroid nodule. Until now, there has been no uniform system for reporting the results of thyroid fine needle aspiration (FNA) in the U.S. The terminology described in this book is an important advance in the field of cytopathology. It represents the results of the multidisciplinary National Cancer Institute Thyroid Fine Needle Aspiration State of The Science Conference, held in Bethesda, MD in October, 2007. The Bethesda System for Reporting Thyroid Cytopathology will provide the reader with a unified approach to diagnosing and reporting thyroid FNA interpretations. It will serve as a reference guide not just for pathologists, but also endocrinologists, surgeons, and radiologists.